2019
DOI: 10.1063/1.5084170
|View full text |Cite
|
Sign up to set email alerts
|

High resolution photoelectron imaging of boron-bismuth binary clusters: Bi2Bn− (n = 2–4)

Abstract: Bismuth boride is a heavy member of the III-V semiconductors. Although there have been some theoretical interests in this material, it has not been synthesized experimentally. Here, we report a high-resolution photoelectron imaging study on a series of boron-bismuth binary clusters, Bi2Bn− (n = 2–4), produced by laser vaporization of a B/Bi mixed target. Vibrationally resolved photoelectron spectra are obtained for all three clusters, and the measured vibrational and electronic information is used to compare w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Thus, only the 6p orbitals are involved in bonding in Bi compounds without sp hybridization. A 6s 2 lone pair is found in all Bi–B binary clusters reported previously. We have analyzed the bonding in BiB n – ( n = 6–8) using AdNDP, as shown in Figures –, respectively. A 6s 2 lone pair is found in each case, whereas the 6p x and 6p y orbitals form two Bi–B σ bonds and the 6p z orbital participates in π bonding with the B n moiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, only the 6p orbitals are involved in bonding in Bi compounds without sp hybridization. A 6s 2 lone pair is found in all Bi–B binary clusters reported previously. We have analyzed the bonding in BiB n – ( n = 6–8) using AdNDP, as shown in Figures –, respectively. A 6s 2 lone pair is found in each case, whereas the 6p x and 6p y orbitals form two Bi–B σ bonds and the 6p z orbital participates in π bonding with the B n moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their large size discrepancy, the bismuth–boron bond is expected to be weak, although very little is known. Only recently have a series of studies focusing on the bismuth–boron bonding been reported in BiBO – , Bi 2 B – , and BiB 2 O – , which are found to contain a single Bi–B, double BiB, and triple BiB bond, respectively. , Other than that, there have been few experimental studies on bismuth–boron species except a recent investigation on the dibismuth boride clusters of Bi 2 B n – ( n = 2–4) …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports of clusters formed by three B atoms showed intriguing bonding and aromaticity. 35–40,44,46 However, since doping B 3 does not lead to any significant modification but rather to an energetic exchange between its two isomers, the linear and the triangular, we begin by describing clusters from four B atoms and, from the lowest to the highest, in our perspective, structural transformation degree. While most experimental techniques have favored the characterization of mainly anionic boron clusters, and in most cases, preceded the characterization of the neutral or cationic counterparts, the order shown for the bare systems is from cations to anions, since the former are the first to show a distortion of the boron skeleton, namely, the 2D to 3D transition.…”
Section: Introductionmentioning
confidence: 99%
“…43 Multiple B 4 clusters doped with one or two heteroatoms are described in the literature. In most cases, the resulting structure maintains a rhomboidal shape of the B moiety with one heteroatom on one edge, bridging two B atoms ( 4-3 ), as in the case of B 4 Pr − , 44 B 4 C − , 45 and bridging two opposite B atoms, as in the case of B 4 Bi 2 − , 46 or directly attached to a B atom, as in B 4 Mg ( 4-4 ). 47 For these examples, the modification in B skeleton is mild, as a result of the electron transfer from dopant to B 4 cluster.…”
Section: Introductionmentioning
confidence: 99%
“…It is a significant milestone in the nanomaterials science that Kroto et al discovered the C 60 fullerene 1 , which aroused a surge of research activities about carbon. As the neighbor of carbon, boron has aroused much research [2][3][4][5][6][7][8] because of its potential application and electron deficiency 9,10 . B 40 11 , the boron analogue of C 60 , has also been experimentally observed 12 .…”
mentioning
confidence: 99%